ChemInform Abstract: Exploiting the π‐Acceptor Properties of Carbene‐Stabilized Phosphorus Centered Trications [L3P]3+: Applications in Pt(II) Catalysis. Issue 13 (18th March 2013) - Carreras, Javier; Patil, Mahendra; Thiel, Walter; Alcarazo, Manuel
Abstract For the first time application of a P1‐centered trication as ligand in catalysis is reported.